2021
DOI: 10.1093/cvr/cvab257
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac natriuretic peptide deficiency sensitizes the heart to stress-induced ventricular arrhythmias via impaired CREB signalling

Abstract: Aims The cardiac natriuretic peptides (atrial natriuretic peptide [ANP] and B-type natriuretic peptide [BNP]) are important regulators of cardiovascular physiology, with reduced natriuretic peptide (NP) activity linked to multiple human cardiovascular diseases. We hypothesized that deficiency of either ANP or BNP would lead to similar changes in left ventricular structure and function given their shared receptor affinities. Methods and Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…2A ). We also included Nppb which encodes brain natriuretic peptide within the MAPK effectors since the hormone mediates the MAPK pathway to regulate cardiac response to stress [ 30 ]. Thus, LPD ESC lines exhibited upregulation of Nppb in RNA sequencing ( P < 0.0001) and confirmed by qRT-PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A ). We also included Nppb which encodes brain natriuretic peptide within the MAPK effectors since the hormone mediates the MAPK pathway to regulate cardiac response to stress [ 30 ]. Thus, LPD ESC lines exhibited upregulation of Nppb in RNA sequencing ( P < 0.0001) and confirmed by qRT-PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further, LPD lines were downregulated in Ddx17 which encodes multitasking RNA helicases that similarly modulate cellular activity from apoptosis to proliferation [ 48 ]. Lastly, LPD lines exhibited upregulation of Nppb encoding B-type natriuretic peptide (BNP) which contributes to MAPK-mediated stress response in cardiomyocytes [ 30 ]. BNP plays a role in cardiac development and elevated plasma levels associate with heart failure and myocardial infarction [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of strong evidence in experimental animals of protean beneficial actions of ANP/BNP across many tissues affecting the integrity of the cardiovascular system [ 2 , 39 ] and the deleterious impact of ablating ANP/BNP pathway activity [ 40 , 41 ], it is unsurprising that circulating concentrations of ANP/BNP products within the normal range have beneficial effects in maintaining cardiovascular and metabolic health in healthy people [ 42 , 43 ]. Whether these subtle differences in plasma concentrations predict subsequent cardiovascular health is the crucial question addressed in this prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired factors such as obesity—lowering BNP [ 19 ]—also need consideration and will be assessed by changes in BMI. Although both ANP and BNP activate the same receptor (NPR1), their variable expression, location, and metabolism highlight the need to measure both bioactive forms in plasma [ 41 ] in associative studies linking levels with changing indicators of vascular, metabolic, and cardiac function in the 15 years after middle age when the incidence of heart disease increases greatly. No other study has examined these relationships in healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings based on genetic diseases also suggest that the MAPK pathway is closely related to heart function and development. Another study found that ANP and BNP maintain myocardial cGMP levels to regulate cardiomyocyte p38 MAPK activity, sensitizing the heart to stress induced ventricular arrhythmias [40]. Recent studies have shown that KLF15 overexpression can reduce cardiomyocyte apoptosis and improve cardiac dysfunction in MI mice partly by inhibiting the p38 /MAPK signaling pathway [41].…”
Section: Discussionmentioning
confidence: 99%